THE EVALUATION OF THE LITERATURE ON HEALTH ECONOMY WITH THE BIBLIOMETRIC ANALYSIS METHOD - Boztosun, Derviş; Doğan, Sermed; Adlı, Fatih (Fırat University, 2022)
The issue of health economics has become a focal point in the literature due to the negativities caused by the epidemics that have global effects and the increase in health expenditures per capita. However, when research on health economics is examined, it is seen that the bibliometric method is very limited. In this context, it is aimed to present a general summary of research on health economics by using the bibliometric analysis method within the scope of the study For this purpose, the articles published in the Social Science Citation Index (SSCI), Science Citation Index Expanded (SCI-EXPANDED), and Emerging Sources Citation Index (ESCI) citation indexes on the Web of Science database between 2011-2021 were accepted as the data set. According to the findings obtained in the study, it was determined that the most used keyword in network analysis was "Health Economics". It has been determined that the journal in which the most articles on health economics are published is “Value in Health” while the most cited journal is “The Lancet”. When the author co-citation network in the field of health economics is examined, it is observed that the most cited work is published by the "World Health Organization". The most cited article in the field of health economics is the study titled “IDF Diabetes Atlas: Global estimates of diabetes prevalence for 2017 and projections for 2045” by Cho et al., (2018). When the institution’s co-authorship analysis is examined in the field of health economics, "England" ranks first with 600 documents of the highest number of studies.

Küresel boyutta etkileri olan salgın hastalıklarının yaratmış olduğu olumsuzluklar ve kişi başına düşen sağlık harcamalarında meydana gelen artış nedeniyle sağlık ekonomisi konusu, alanyazında odak noktası haline gelmiştir. Ancak sağlık ekonomisi alanına yönelik gerçekleştirilen araştırmalar incelendiğinde bibliyometrik yönteme çok kısıtlı bir şekilde yer verildiği görülmektedir. Bu bağlamda çalışma kapsamında bibliyometrik analiz yöntemi kullanılarak sağlık ekonomisini konu alan araştırmaların genel bir özetinin sunulması amaçlanmaktadır. Bu amaç doğrultusunda 2011-2021 yılları arasında Web of Science veri tabanı üzerinde Social Science Citation Index (SSCI), Science Citation Index Expanded (SCI-EXPANDED), Emerging Sources Citation Index (ESCI) atıf indekslerinde yayımlanmış makaleler veri seti olarak kabul edilmiştir. Çalışmada elde edilen bulgulara göre ağ analizinde en fazla kullanılan anahtar kelime “Health Economics” olduğu belirlenmiştir. Sağlık ekonomisi ile ilgili en fazla makalenin yayımlandığı dergi “Value in Health” dergisi iken en fazla atıf alan dergi ise “The Lancet” dergisi olduğu tespit edilmiştir. Sağlık ekonomisi alanında yazar ortak atıf ağı incelendiğinde en fazla atıf alan çalışmanın “World Health Organization” tarafından gerçekleştirilen yayınlara yer verildiği gözlenmektedir. Sağlık ekonomisi alanında en fazla atıf alan makale Cho vd. (2018) tarafından yapılan “IDF Diabetes Atlas: Global estimates of diabetes prevalence for 2017 and projections for 2045” başlıklı çalışması ile ilk sırada yer almaktadır. Sağlık ekonomisi alanında kurum ortak yazarlık analizi incelendiğinde en fazla çalışmanın 600 doküman ile “İngiltere” ilk sırda yer almaktadır.
SAĞLIK EKONOMİSİNE YÖNELİK ALANYAZININ BİBLİYOMETRİK ANALİZ YÖNTEMİ İLE DEĞERLENDİRİLMESİ